Enhanced Cell Osteogenic Differentiation in Alendronate Acid and Flufenamic Acid Drug-Impregnated Nanoparticles of Mesoporous Bioactive Glass Composite Calcium Phosphate Bone Cement In Vitro - Shih-Ming Liu; Jian-Chih Chen; Ssu-Meng Huang; Shang-Hong Lin; Wen-Cheng Chen (MDPI AG, 2023)
This study aims to compare the anti-osteoporotic drugs alendronic acid (ALN) and flufenamic acid (FA) alone impregnate into nanoparticles of mesoporous bioactive glass (nMBG), which further composites calcium phosphate cement (CPC) and investigates their in vitro performance. The drug release, physicochemical properties, and biocompatibility of nMBG@CPC composite bone cement are tested, and the effect of the composites on improving the proliferation and differentiation efficiency of mouse precursor osteoblasts (D1 cells) is also investigated. Drug release shows that FA impregnates nMBG@CPC composite, a large amount of FA is released rapidly within 8 h, gradually reaching a stable release within 12 h, followed by a slow and sustained release within 14 days, and then reaches a plateau within 21 days. The release phenomenon confirms that the drug-impregnated nBMG@CPC composite bone cement effectively achieves slow drug delivery. The working time and setting time of each composite are within 4-10 min and 10-20 min, respectively, meeting the operational requirements of clinical applications. The addition of nMBG nanoparticles in the CPC matrix did not prevent the aggregation phenomenon under microstructural observation, thus resulting in a decrease in the strength of the nMBG@CPC composite. However, after 24 h of immersed reaction, the strength of each 5 wt.% nMBG impregnated with different concentrations of FA and ALN is still greater than 30 MPa, which is higher than the general trabecular bone strength. The drug-impregnated nMBG@CPC composites did not hinder the product formation and exhibit biocompatibility. Based on the proliferation and mineralization of D1 cells, the combination of nMBG with abundant FA and ALN in CPC is not conducive to the proliferation of D1 cells. However, when D1 cells are contact cultured for 21 days, alkaline phosphatase (ALP) enzyme activity shows higher ALP secretion from drug-impregnated nMBG@CPC composites than drug-free composites. Accordingly, this study confirms that nMBG can effectively impregnate the anti-osteoporosis drugs FA and ALN, and enhance the mineralization ability of osteoblasts. Furthermore, drug-impregnated nMBG applications can be used alone or in combination with CPC as a new option for osteoporotic bone-filling surgery.